Influence of Temperature Sensor (Pt100) Accuracy on the Interpretation of Experimental Results of Measuring Temperature on the Surface - Małek, Maria Teresa; Koczyk, Halina (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article presents the impact of accuracy of sensors, or more specifically Pt100 temperature sensors, on result analysis of experimental studies. For this purpose, an experiment was carried out consisting in measuring the temperature on the surface of a partition - a concrete wall, beneath its insulation layer. The tested surface was separated from external environment and could only be influenced by the wall structure. Therefore, the expected result of the experiment, i.e. the difference in temperature sensor readings in identical locations on both sides of the partition, should reach a value close to 0.
Keywords: temperature measurement; absolute error; Pt100 temperature sensors; pipe-embedded wall; experimental measurements; box and whisker plot